Analisis Perbedaan Keterampilan Servis, Smash, Blok, dan Chop antara Atlet Tenis Meja Putra dan Putri di Kabupaten Kolaka - Rahedin Suwo; Nofi Marlina Siregar; Novri Asri (Indonesian Journal of Physical Education and Sport Science, 2026)
Study purpose. This study aimed to describe the basic table tennis skill profile of student athletes in Kolaka Regency and to compare the performance of male and female athletes across four fundamental technical components: serve, smash, block, and chop. Materials and methods. This study employed a descriptive quantitative approach with a cross-sectional design. A total of 25 student athletes (13 males and 12 females) from table tennis training programs in Kolaka Regency participated in the study. Basic technical skills were assessed using a validated instrument covering four components: serve, smash, block, and chop. Descriptive statistics were used to identify the overall skill profile, while independent sample t-tests were conducted to compare male and female athletes in each component. Effect sizes were calculated using Cohen’s d, and 95% confidence intervals were reported to complement the significance testing. Results. The results showed that the athletes were generally at an intermediate level of basic technical proficiency. Among the four components, serve had the highest mean score, whereas chop was the weakest skill component. Significant differences between male and female athletes were found in smash (p = .031, d = 0.92) and chop (p = .021, d = 0.99), with male athletes obtaining higher scores in both components. In contrast, no significant differences were observed in serve (p = .231) and block (p = .598). The total score comparison showed a medium-to-large effect size (d = 0.67), although the difference did not reach statistical significance (p = .109), indicating that the result should be interpreted cautiously. Conclusions. Student athletes in Kolaka Regency generally demonstrated intermediate-level basic table tennis skills, with stronger performance in serve and weaker performance in chop. Differences between male and female athletes were not evident across all skill components, but were more pronounced in smash and chop. These findings provide an initial empirical basis for evaluating athlete performance and for supporting more targeted coaching practices in the local context. However, the results should be interpreted with caution due to the relatively small sample size and the cross-sectional design of the study..